Research progress of neoantigen-based dendritic cell vaccines in pancreatic cancer - Zhang, Xin; Xu, Zheng; Dai, Xiangpeng; Zhang, Xiaoling; Wang, Xueju (Frontiers in Immunology, 2023)
Mutation of the crucial genes such as tumor suppressors or oncogenes plays important role in the initiation and development of tumors. The non-synonymous mutations in the tumor cell genome will produce non-autologous proteins (neoantigen) to activate the immune system by activate CD4+ and CD8+ T cells. Neoantigen-based peptide vaccines have exhibited exciting therapeutic effects in treating various cancers alone or in combination with other therapeutic strategies. Furthermore, antigen-loaded DC vaccines are more powerful in inducing stronger immune responses than vaccines generated by antigens and adjuvants. Therefore, neoantigens based Dendritic cell (DCs) vaccines could achieve promising effects in combating some malignant tumors. In this review, we summarized and discussed the recent research progresses of the neoantigen, neoantigen-based vaccines, DC-based vaccine in pancreatic cancers. The combination of neoantigen and DC-based vaccine in pancreatic cancer was also highlighted. Therefore, our work will provide more detailed evidences and novel opinions to promote the development of personalized neoantigen-based DC vaccine for pancreatic cancer.